2003
DOI: 10.1016/s0014-5793(03)00525-8
|View full text |Cite
|
Sign up to set email alerts
|

Occludin phosphorylation: identification of an occludin kinase in brain and cell extracts as CK2

Abstract: In epithelial and endothelial cells, tight junctions limit paracellular £ux of ions, proteins and other macromolecules. However, mechanisms regulating tight junction function are not clear. Occludin, a tight junction protein, undergoes phosphorylation changes in several situations but little is known about occludin kinases. A recombinant C-terminal fragment of occludin is a substrate for a kinase in crude extracts of brain. This activity was puri¢ed about 10 000-fold and identi¢ed as CK2 (casein kinase 2) by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 25 publications
(35 reference statements)
3
34
0
Order By: Relevance
“…Similar results have been observed with multiple experimental systems [105,116,120]. Phosphoamino acid analysis of brain extracts [99] as well as endothelial cell [116] and MDCK cell [121] lysates suggest that occludin is primarily phosphorylated on serine and threonine residues and that the slower migrating, hyperphosphorylated form of occludin is associated with phosphorylation on multiple serine residues [121]. Using mass spectrometry of occludin immunoprecipitated from vascular endothelial cells, Sundstrom et al identified five putative occludin phosphosites and in vivo phosphorylation of Ser490 was validated using a phosphospecific antibody (manuscript submitted).…”
Section: Occludin Phosphorylation and Permeabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results have been observed with multiple experimental systems [105,116,120]. Phosphoamino acid analysis of brain extracts [99] as well as endothelial cell [116] and MDCK cell [121] lysates suggest that occludin is primarily phosphorylated on serine and threonine residues and that the slower migrating, hyperphosphorylated form of occludin is associated with phosphorylation on multiple serine residues [121]. Using mass spectrometry of occludin immunoprecipitated from vascular endothelial cells, Sundstrom et al identified five putative occludin phosphosites and in vivo phosphorylation of Ser490 was validated using a phosphospecific antibody (manuscript submitted).…”
Section: Occludin Phosphorylation and Permeabilitysupporting
confidence: 88%
“…The proximal C-terminus includes amino acids 266-412 but has not been formally associated with a domain or conserved functional motif. The proximal region has been shown to be phosphorylated by casein kinase I [97], casein kinase II [97][98][99] and by protein kinase C [100]. Unfortunately, these phosphorylation sites have not been confirmed in vivo.…”
Section: Occludin and Tricellulinmentioning
confidence: 99%
“…Casein kinase 2 (CK2) phosphorylated OCC at T375 and S379, 41 and in vitro studies pointed to CK2 as OCC kinase. 42 However, the paucity of the phosphorylation sites by PKC contrasted with the multiple phosphorylation residues found in previous reports 8 suggesting the involvement of other kinases in this process. In addition, OCC could be phosphorylated on tyrosine residues by src-like tyrosine kinase, c-Yes.…”
Section: Discussionmentioning
confidence: 79%
“…and IV.C.3, we provide a summary and critical discussion on the role of several protein kinases on Sertoli cell BTB function and how these kinases regulate BTB restructuring during the seminiferous epithelial cycle in concert with cytokines, actin regulators, and steroids. However, it must be noted that several other nonreceptor protein kinases [e.g., CK1 (casein kinase 1) and CK2, which are also found at the BTB associating with the N-cadherin/␤-catenin complex but not with nectin/afadin ] (Cordenonsi et al, 1997(Cordenonsi et al, , 1999Smales et al, 2003;Dörfel et al, 2009) and GTPases (e.g., Rho kinase) (Yamamoto et al, 2008), can also regulate the phosphorylation status of occludin, tricellulin, or claudin-5 and adhesion in other epithelia and blood-tissue barriers (e.g., the blood-brain barrier).…”
Section: Nonreceptor Protein Kinases: Focal Adhesionmentioning
confidence: 99%